2012
DOI: 10.1590/s0365-05962012000100025
|View full text |Cite
|
Sign up to set email alerts
|

Case for diagnosis

Abstract: Dyschromicum erythema perstans, or ashy dermatosis, is a rare chronic acquired skin disease characterized by gray hyperpigmented patches with erythematous borders. Its etiology is unknown and there is no specific treatment for the condition. We report a case of ashy dermatosis in a 41-year-old patient with extensive lesions on the trunk and limbs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The most difficult differential diagnosis is with ashy dermatosis, this, however, affects brown skinned patients, with a tropism for the torso and limbs (and not for intertriginous areas) and with erythematous borders on the edges of active lesions. 1,3,5-8 Microscopically, one can observe a lichen planus in regression. There is epidermic atrophy with irregular hydropic degeneration on the basal layer and an absence of epidermic hyperplasia (usually present on lichen planus).…”
Section: Discussionmentioning
confidence: 99%
“…The most difficult differential diagnosis is with ashy dermatosis, this, however, affects brown skinned patients, with a tropism for the torso and limbs (and not for intertriginous areas) and with erythematous borders on the edges of active lesions. 1,3,5-8 Microscopically, one can observe a lichen planus in regression. There is epidermic atrophy with irregular hydropic degeneration on the basal layer and an absence of epidermic hyperplasia (usually present on lichen planus).…”
Section: Discussionmentioning
confidence: 99%
“…Such morphological findings, though subtle, suggest the clinical hypothesis ashy dermatosis (Persistent Dyschromatic Erythema) as well as postinflammation pigmentation. 4 Lightening lotion (Arbutin 4%, Chromabright 0.5%, Alf abisabol 1%, Nicotinamide 4%, Kojico Acid 3%, Nonionic Cream) was then prescribed por use at night on all spots, and after 30 days, it was observed that lightening of the macules and skin rejuvenation occurred. However, there was no lightening of the inframammary region and of the upper limbs' macules.…”
Section: Case Reportmentioning
confidence: 99%
“…This border is present in acute lesions, but may be replaced by a hypochromic halo. [4][5][6][7][8][9][10][11][12] An important fact is that ashy dermatosis appears more often in patients with darker colored skin, but the patient reported is white.…”
Section: Ashy Dermatosismentioning
confidence: 99%
See 1 more Smart Citation
“…EDP, also known as ashy dermatosis, is a rare acquired idiopathic hypermelanosis. The etiology remains unknown, however several predisposing factors have been proposed, such as drugs (antibiotics, benzodiazepines, pesticides), endocrinopathies or infectious disorders such as human immunodeficiency virus infection and hepatitis C. 4 - 6 The main differential diagnosis of EDP is pigmented lichen planus (usually shiny purple, flat-topped, firm papules often crossed by fine white lines) however, lichen planus often involves mucous membranes and is associated with mild pruritus, neither characteristics were present in this boy. Idiopathic eruptive macular pigmentation would be another differential hypothesis, however this condition shows typically with brownish and non confluent lesions.…”
mentioning
confidence: 99%